PENGARUH MODAL MINIMAL, PELATIHAN PASAR MODAL DAN RISIKO INVESTASI TERHADAP MINAT INVESTASI MAHASISWA DI KOTA BATAM - Windyarini, Nurika Putri; Tobing, Vargo Christian L (LPPM Universitas Putera Batam, 2025)
This study aims to determine the influence of minimum capital, capital market training, and investment risk on the investment interest of accounting students in Batam City. The background of this research is based on the low level of student participation in investment, despite the increasing opportunities in the capital market due to easier access and low initial capital requirements. This research employs a quantitative approach using a survey method. The sampling technique used is simple random sampling, with a total of 95 student respondents from five universities in Batam City. Data were collected through questionnaires developed based on indicators of each variable, and then analyzed using SPSS version 31. The results show that minimum capital has no significant effect on investment interest. Capital market training also does not have a significant effect on investment interest. However, investment risk has a positive and significant effect on investment interest. Simultaneously, the three variables have a significant influence on students' investment interest. The Adjusted R Square value of 0.116 indicates that the independent variables in this study explain 11.6% of the variation in investment interest, while the remaining percentage is influenced by other factors outside the research model.